Identitas dalam Kebijakan Luar Negeri: Studi Kasus Peran Norwegia sebagai Peace Nation dalam Upaya Perdamaian Israel – Palestina - Agnes, Pretty; Rosyidin, Mohamad (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
For many years, the increasing number of death and regional damage as the effects of Israel-Palestine’s prolonged conflict has been an international threat to world peace. This phenomenon encourages international relations actors to contribute in the peace efforts for two involved countries, including Norway. The contribution of Norway is realized by its involvement in Oslo Accord and the Ad Hoc Liasion Committee (AHLC), and also from another Norway’s foreign policies. This research aims to explain the purpose behind the foreign policy of Norway that tends to the efforts of Israel-Palestine’s conflict. By using the constructivism approach, specifically the role-concept, this study emphasizes the Norway’s role as a peace nation. This research concludes that the foreign policies of Norway in Israel – Palestinian conflict resolution is a representation of Norway’s identity as a peace nation.